Use of reclaimed urban wastewater for the production of hydroponic barley forage: water characteristics, feed quality and effects on health status and production of lactating cows - Ceci, Luigi; Cavalera, Maria Alfonsa; Serrapica, Francesco; Di Francia, Antonio; Masucci, Felicia; Carelli, Grazia (Frontiers in Veterinary Science, 2023)
The safety of reclaimed urban wastewater (RUW) for the production of hydroponic barley forage (HBF) was evaluated in terms of effluent and forage characteristics, as well as the health and performance of lactating cows. The study was conducted on a dairy farm equipped with two hydroponic chambers producing approximately 620 kg/d of HBF as fed. For experimental purposes, HBF was produced using RUW collected from an aqueduct plant processing urban wastewater in a membrane bioreactor treatment chain. A feeding trial was carried out with HBF derived from RUW. Sixty lactating cows were randomly assigned to two balanced groups fed a standard total mixed ration (TMR) or a TMR in which 10 kg of HBF replaced 1 kg of oat hay and 0.5 kg of maize. The experimental period lasted 7 weeks, including a 2-week adaptation period, during which each cow underwent a physical examination, BCS scoring, blood sampling for a complete blood count and biochemical panel, recording of body weight and milk yield and quality, including fatty acid composition and heavy metal content. Ruminal pH was continuously monitored by reticulorumen boluses, and nutrient digestibility and N balance were determined at week 7. RUW showed an acceptable microbial load and an overall good quality as irrigation water, even though the supply of N and P did not influence the yield and quality of HBF. The characteristics of HBF reflected the quality of RUW supplied to the hydroponic chambers and no anomalous components (i.e., high ion concentration) were found. Feeding RW-derived HBF to lactating cows had no major positive or negative effects on animal health and production, including milk quality, ruminal pH, in vivo digestibility, and N balance. The use of RUW under the conditions tested appears to be safe for the health status of lactating cows and the quality of the milk obtained. Overall, the results do not reveal any major limitations for the use of tertiary wastewater as irrigation water for the hydroponic production of forage barley, so that a wider use of wastewater in hydroponic systems seems realistic.